The long job: Pound, Dante and the epic ambition - Sarı, Dilara. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
The legacy of Ezra Pound has long been a source of awe, disturbance and confusion; more so than almost any other poet of the modern age. The Cantos serves as the foundation to that legacy as representative of decades-long sadness, conflict, isolation, and hope. Various critical discussions surrounded the work ever since its publication as a whole, but more often than not, The Cantos is treated as a thing of the past: as an accumulation of ancient knowledge, immersed with myths no longer in fashion, pining after a world that was to never exist. This work argues that despite such reputation, The Cantos possesses a great dynamism, a moving force that hopes alter the society, and the human civilization, into which it was born. In order to understand its potential better, The Cantos should be approached as an expression of the same ambition that drives the pages of Dante Alighieri’s Divine Comedy. These two epics share a clear representation of the faults of contemporary times, an insistence on directness and precision, and an emphasis on intellectuality as the saving force. Looking at The Cantos through the light provided by The Divine Comedy helps us to better situate the epic ambition of the work, and to comprehend the dynamic desire to initiate change that is inherent in Pound’s magnum opus.